Thioether‐Containing Copper Complexes as PHM, DβM, and TβM Model Systems. Issue 1 (25th October 2021) - Gómez‐Vidales, Virginia; Castillo, Ivan
Abstract: This minireview presents efforts of synthetic chemists to mimic the active site of the copper monooxygenase enzymes peptidylglycine α‐hydroxylating monooxygenase (PHM), dopamine β‐monooxygenase (DβM), and tyramine β‐monooxygenase (TβM), all of which feature copper‐thioether ligation in their resting states. These monooxygenases are involved in the initial activation of O2 to generate neurotransmitters by the selective activation of C−H bonds of their corresponding substrates, resulting in subsequent hydroxylation. Attempts to emulate the N2 S donor set provided by the two histidines and the methionine residues that coordinate to copper in the active site employ N2 S and N3 S ‐type ligands, with the latter ones providing the best conditions for testing the reactivity of their Cu I complexes with dioxygen. Identification of Cu II ‐superoxos as capable agents for C−H activation has provided support for these species as the key reactive intermediates in the enzymatic systems. Synthetic end‐on [Cu II ‐η 1 ‐O2. − ] and side‐on [Cu II ‐η 2 ‐O2. − ] cupric superoxos are capable of such transformations, which is related to the open question of whether the methionine S ‐donor may act as a hemilabile ligand in biological systems. Abstract : PHM, DβM, and TβM are copper monooxygenases with methionine S ‐donors that generate neurotransmitters by O2 and C−H bond activations. N2 S and N3 S ligands provide synthetic copper systems that mimic enzymatic properties, among which ( N3 S )Cu II ‐superoxos emulate the key biological reactive intermediates. The methionine thioether donors modulate the electronic properties of the Cu centers and may act as hemilabile ligands.